AI powered ELT: Instructors’ transformative roles and opportunities - Afnan Almegren; Rehan Megren Almegren; Abduljalil Nasr Hazaea; Hassan Saleh Mahdi; Jamal Kaid Mohammed Ali (PLoS ONE, 2025)
The integration of artificial intelligence (AI) in education is reshaping English language teaching (ELT), redefining the ‘assistant’ function of technology and the ‘interaction’ roles of language instructors. This study specifically investigates instructors’ roles in AI-powered learning environment and its benefits for ELT. It develops a conceptual framework for AI powered ELT. Using a qualitative approach, data were gathered through online focus group discussions with 22 instructors from different regions. The thematic analysis revealed that AI empowers ELT by enabling personalized teaching, mono-active language practice, increased productivity, automated feedback and assessment, and adaptive material creation. Additionally, instructors assume four key roles: evolving facilitators, blended role practitioners, flexible material designers, and creative prompters. These transformations reflect a departure from the assistant function and the facilitator roles cantered on human interaction to more mono-active roles aligned with AI-powered innovations. The study highlights the necessity for ELT to embrace these new roles to effectively navigate the evolving dynamics of ELT in the different region in the AI era. Acknowledging its qualitative limited scope, the study recommends further broader research on these transformations with specific attention to language skills.